IMPLEMENTATION OF SUSTAINABLE PERFORMANCE THROUGH THE GREEN RELATIONAL CAPITAL AND GREEN INNOVATION MODELS - Rokhman, M Taufiq Noor; Ratnawati, Ratnawati; Yuliana, Rachma (Proceedings of the International Conference of Islamic Economics and Business (ICONIES); Vol 11 No 1 (2025): The 11th International Conference of Islamic Economics and Business (ICONIES 2025), 2025)
The purpose of this study is to explore the influence of green relational capital and green innovation on sustainable performance, developed within a single model and explained through the Resource-Based Theory (RBT) as the main theoretical framework. The research sample consisted of 193 micro, small, and medium enterprises (MSMEs). Data were analyzed using the structural equation model with Partial Least Squares (PLS). The findings indicate that both green relational capital and green innovation significantly affect sustainable performance. This research contributes to the Resource-Based Theory by demonstrating that MSMEs are able to transform their resources into capabilities that foster green relational capital, such as two-way communication with customers, suppliers, networks, and partners regarding environmental management, as well as eco-friendly innovations. These practices enable businesses to generate profit and sustain a competitive advantage